Analysis of 2D DNA Origami with Nanopipettes. Issue 20 (21st August 2018) - Raveendran, Mukhil; Lee, Andrew J.; Wälti, Christoph; Actis, Paolo
Abstract: Nanopipettes are a useful tool for the detection and analysis of biological molecules at the single‐molecule level. Here, we employ nanopipettes fabricated from glass capillaries to identify differently structured 2D DNA origami through the distinctive amplitude and dwell time of the ion current peak resulting from the translocation of the origami through the nanopipette pore. We demonstrate that the ion current peak originating from frame‐like DNA origami comprises two individual peaks in contrast to solid tiles of similar size that only lead to a single peak in the ion current. Interestingly, the fine details of the shape of the double‐peak characteristic of the translocation of DNA origami frames are correlated with the structural features of the DNA origami. In particular, the size of the central cavity governs the lag time between the two constituent peaks of the double‐peak. This work demonstrates the ability of glass nanopipettes to identify and characterize differently structured DNA origami of similar size, advancing the potential of nanopipettes for high‐sensitivity single‐molecule studies. Abstract : DNA origami : Glass nanopipettes with sub‐100 nm pore diameters can detect structural and geometrical variations between different DNA origami. The shape of the translocation‐induced ion current peak can be used as a fingerprint to distinguish frame‐shaped from solid tile‐shaped DNA origami.